PERANCANGAN IMPLEMENTASI E-LEARNING BERBASIS MOODLE DALAM MATAKULIAH APLIKASI KOMPUTER PROGRAM STUDI ILMU GIZI UPERTIS - Harleni Harleni; Nova Mustika (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
The research was conducted with the aim of designing a Moodle-based e-learning implementation in the form of a website in the Computer Applications subject in the Nutrition Science study program. This e-learning system is designed to be implemented in all courses in the Nutrition Science study program, thus helping lecture activities. As an initial development, this e-learning system was tested in the Computer Application course. This study uses a research and development design (Research and Development) according to Sugiyono (2010). The research subjects were Computer Application lecturers and students who had attended Computer Application lectures determined by purposive sampling. The data taken is the feasibility of the material and media through a questionnaire, and student responses through a questionnaire. Expert response shows that Moodle-based e-learning is very good in terms of media and good in terms of material. The results of the student response questionnaire on small-scale trials showed that the majority of students gave positive responses to learning activities using Moodle-based e-learning media. The final Moodle-based e-learning product contains modules, video, ppt, chat, virtual classes and discussion forums. Various content and facilities that the e-learning has developed make Learning Motion Systems more interesting. Based on the results of the analysis and discussion, it can be concluded that Moodle-based e-learning is appropriate and feasible to be applied to the Computer Application course.